Role of Consumption intent in Service Quality Perceived Benefit Relationship - Nattuvathucka Barnabas; Mekoth Nandakumar, Sony Michael (New Delhi Indian Journal of Marketing, 2020)
The Purpose of this study was two-fold. First, it explained the relationship between service quality and benefit perception. Second, it studied the role of customers' intent in the relationship. Following a descriptive design, data were gathered from a sample of 202 restaurant customers in Goa, India during the year 2017.The areas of Practical relevance included perception, and adaptations in service design and delivery to address customer induces variability.
Keywords: Marketing